The Space Between Us: Questioning Multi-Spatial Justice in the Upcoming Indonesia’s Capital - Listiningrum, Prischa; Al Anwary, Muhammad Anis Zhafran; Widiarto, Aan Eko; Susmayanti, Riana; Nurosidah, Sherlita (Journal of Human Rights, Culture and Legal System, 2023)
Land is not only defined as an object of ownership by certain community groups, especially indigenous communities. Land has intrinsic value inherent in the way of life and culture, thus affecting the quality of life. This article examines the potential implications of the land acquisiton process in the prospected Nusantara Capital in regards to the fulfillment of the right to an adequate standard of living. It is reviewed by engaging multi-spatial justice within the context of city development and urban transformation with learning lessons from Brasilia and Jakarta. Utilizing a qualitative socio-legal approach, the research employs systematic and structural interpretation of various legal instruments. It incorporates the concept of multi-spatial justice as part of a critical legal geography and urban sociology theory to understand the potential of segregation and gentrification in the Nusantara Capital. The results highlight three key aspects. Firstly, the concept of multi-spatial justice underscores the need to consider diverse spatial entities and their equitable treatment. Secondly, analyzing the State Capital Law reveals both promising and concerning aspects of spatial justice. While it aims to balance development and inclusivity, inconsistencies within the law's provisions raise concerns about potential injustices. Lastly, the study anticipates future inequities between local and urban spatials due to unequal land compensation. These findings emphasize the importance of addressing procedural and substantive fairness in land acquisition, fostering inclusive urban development, and aligning legal instruments with principles of multi-spatial justice.